1974
DOI: 10.1113/jphysiol.1974.sp010435
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of corneal hydration by a salt pump requiring the presence of sodium and bicarbonate ions

Abstract: SUMMARY1. The use of polyacrylamide gel salt bridges enables trans-membrane potentials to be measured to an accuracy of 20 /tV over long periods. 2.The technique is applied to measure electrical potentials across corneal endothelia of rabbits.3. In de-epithelialized corneas which translocate water, a spontaneous potential of 550 1V is found across the endothelium (tissue resistance 20 Q cm2).4. This electrical potential (and water translocation) is reduced to zero when sodium is absent from the Ringer, and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 26 publications
6
63
0
Order By: Relevance
“…In addition, that flux is in all likelihood transcellular, given that it takes place against a small but significant voltage gradient across the endothelium (ϳ500 V, aqueous negative; Refs. 4,11,12,17 (20) proposed a Na ϩ -HCO 3 Ϫ -coupled exit. Bonanno and Giasson (7) gave arguments for an alternative mechanism based on a role of an apical Cl Ϫ /HCO 3 Ϫ exchanger.…”
mentioning
confidence: 99%
“…In addition, that flux is in all likelihood transcellular, given that it takes place against a small but significant voltage gradient across the endothelium (ϳ500 V, aqueous negative; Refs. 4,11,12,17 (20) proposed a Na ϩ -HCO 3 Ϫ -coupled exit. Bonanno and Giasson (7) gave arguments for an alternative mechanism based on a role of an apical Cl Ϫ /HCO 3 Ϫ exchanger.…”
mentioning
confidence: 99%
“…chloride transport; cAMP; CFTR phosphorylation THE CORNEAL ENDOTHELIUM MAINTAINS the hydration and optical transparency of the cornea by continuously secreting fluid in opposition to a leak driven by tissue swelling pressure generated by stromal glycosaminoglycans. Endothelial fluid secretion is dependent on the presence of HCO 3 Ϫ (15,18,34) and Cl Ϫ (34,47) and is slowed in the presence of carbonic anhydrase inhibitors (18,19,27). Tracer flux studies have shown that net basal to apical HCO 3 Ϫ (19,21,45) and Cl Ϫ (21) transport can contribute to the small (Ϫ0.5 mV) apical-side negative transepithelial potential; however, the relative contribution of each anion is unclear.…”
mentioning
confidence: 99%
“…Second, aldehyde fixatives always destroy the ultrastructure of the corneal endothelium (Hodson, 1968(Hodson, , 1969a. The methods of achieving the four transport modes are fully described in Hodson (1971 a), Dikstein & Maurice (1972), Maurice (1972), Hodson (1974) and Hodson & Miller (1976). For purposes of convention the active bicarbonate flux is nominated 3B and positive values indicate a current of bicarbonate ions out of the cornea across the endothelium into the lens-side.…”
Section: Methodsmentioning
confidence: 99%